Client feedback program - Kelley, Sharit Melissa (My University, 2015)
This project represents a three-part program aimed at enhancing the efficiency and effectiveness of a Marriage and Family Therapy training clinic. This report begins with a review of literature and research regarding established response measures. The research component will also address the importance of self-report by clientele and the issue of early termination of the therapeutic process. A combined faculty and staff effort will establish a means of gaining immediate client feedback regarding the treatment program. Suggestions will be made as far as the implementation of the response policy. As implemented, the therapist or therapist team might amend and adjust the treatment plan to better suit the needs, desires and comfort levels of the client unit.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Kelley, S. M. (2002). Client feedback program. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Marital psychotherapy; Family psychotherapy; Psychotherapist and patient; Psychotherapy--Termination; Reports; Reports